2017
DOI: 10.1002/iid3.202
|View full text |Cite
|
Sign up to set email alerts
|

Environmental levels of avian antigen are relevant to the progression of chronic hypersensitivity pneumonitis during antigen avoidance

Abstract: BackgroundIn chronic hypersensitivity pneumonitis (chronic HP), antigen avoidance is critical for disease management; however, complete avoidance is difficult because of unrecognized exposure to antigens. Recently, we revealed that the amount of avian antigen (AAA) in household dust at the time of diagnosis predicted the progression of chronic bird‐related HP. The purpose of this study is to evaluate the relationship between the prognosis of chronic bird‐related HP and the AAA that remained in the environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…We confirmed the exposition to birds' antigens in 60% of HP patients, to hay or hay products in 49%, and to any of above mentioned antigens in 77% of patients. These data are in agreement with observations from other studies where birds' antigens were responsible for the most HP cases in their series [12,13].…”
Section: Discussionsupporting
confidence: 93%
“…We confirmed the exposition to birds' antigens in 60% of HP patients, to hay or hay products in 49%, and to any of above mentioned antigens in 77% of patients. These data are in agreement with observations from other studies where birds' antigens were responsible for the most HP cases in their series [12,13].…”
Section: Discussionsupporting
confidence: 93%
“…In another study, CT findings of airspace consolidation and honeycombing were found to be predictive of mortality in chronic HP [6]. From another perspective, the levels of exposure to avian antigen have been found to be related to disease progression and prognosis in chronic bird-related HP [7, 8]. To date, there are no established biomarkers to predict the worsening of lung function.…”
Section: Introductionmentioning
confidence: 99%
“…The mainstay of management for BFL is antigen avoidance and steroid treatment 58 . If the amount of avian antigen is not reduced, the patients’ pulmonary function could dramatically decline 59 . Steroid treatment is also expected to improve lung function in BFL patients 60 .…”
Section: Discussionmentioning
confidence: 99%